PERBANDINGAN KINERJA METODE AVERAGE LINKAGE DAN WARD DALAM PENGELOMPOKAN TINGKAT KESEJAHTERAAN MASYARAKAT PROVINSI SUMATERA BARAT MENURUT KABUPATEN/KOTA TAHUN 2021 - Riska Ramadani; Admi Salma (UNIVERSITAS NEGERI PADANG, 2022)
Welfare in West Sumatra Province is still an important problem that is being faced the whole community in 2021. The government is still trying to improve performance the welfare of the community from all aspects. It is necessary to grouping the level of community welfare in the Province of West Sumatra by Regency/City using the average linkage and Ward methods. The results of the cluster analysis obtained by both methods show that the clusters formed are same but objects in the clusters are different. Consists of 3 clusters, namely cluster 1 with a low level of welfare, cluster 2 with a medium level of welfare and cluster 3 with a high level of welfare. Of the two methods, the average linkage method is better in grouping than Ward method the levels of welfare based on validity because it has a large Dunn Index value is 0,88 and a small Connectivity value is 5,85